Excellent Silicon Surface Passivation Achieved by Industrial Inductively Coupled Plasma Deposited Hydrogenated Intrinsic Amorphous Silicon Suboxide - Jia Ge; Muzhi Tang; Johnson Wong; Zhenhao Zhang; Torsten Dippell; Manfred Doerr; Oliver Hohn; Marco Huber; Peter Wohlfart; Armin G. Aberle; Thomas Mueller (International Journal of Photoenergy)
We present an alternative method of depositing a high-quality passivation film for heterojunction silicon wafer solar cells, in this paper. The deposition of hydrogenated intrinsic amorphous silicon suboxide is accomplished by decomposing hydrogen, silane, and carbon dioxide in an industrial remote inductively coupled plasma platform. Through the investigation on CO2 partial pressure and process temperature, excellent surface passivation quality and optical properties are achieved. It is found that the hydrogen content in the film is much higher than what is commonly reported in intrinsic amorphous silicon due to oxygen incorporation. The observed slow depletion of hydrogen with increasing temperature greatly enhances its process window as well. The effective lifetime of symmetrically passivated samples under the optimal condition exceeds 4.7 ms on planar n-type Czochralski silicon wafers with a resistivity of 1 Ωcm, which is equivalent to an effective surface recombination velocity of less than 1.7 cms−1 and an implied open-circuit voltage (Voc) of 741 mV. A comparison with several high quality passivation schemes for solar cells reveals that the developed inductively coupled plasma deposited films show excellent passivation quality. The excellent optical property and resistance to degradation make it an excellent substitute for industrial heterojunction silicon solar cell production.